2021
DOI: 10.1097/sla.0000000000004915
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Decision-Making in Pancreatic Ductal Adenocarcinoma

Abstract: Objective: To develop a predictive model of oncologic outcomes for patients with pancreatic ductal adenocarcinoma (PDAC) undergoing resection after neoadjuvant or induction chemotherapy use. Background: Early recurrence following surgical resection for PDAC is common. The use of neoadjuvant chemotherapy prior to resection may increase the likelihood of long-term systemic disease control. Accurately characterizing an individual's likely oncologic outcome in the perioperative setting remains challenging. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Still, both the NCCN and ASCO clinical practice guidelines recommend clinicians consider administering postoperative chemotherapy after resection even if NAT was previously administered [24, 25]. In such circumstance, identifying patient populations likely to benefit from additional chemotherapy may prove helpful [32]. Like this study, van Roessel et al also noted a survival advantage associated with additional postoperative chemotherapy in patients with node‐positive disease [33].…”
Section: Discussionmentioning
confidence: 75%
“…Still, both the NCCN and ASCO clinical practice guidelines recommend clinicians consider administering postoperative chemotherapy after resection even if NAT was previously administered [24, 25]. In such circumstance, identifying patient populations likely to benefit from additional chemotherapy may prove helpful [32]. Like this study, van Roessel et al also noted a survival advantage associated with additional postoperative chemotherapy in patients with node‐positive disease [33].…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, ESPAC‐5F trial demonstrated that neoadjuvant mFOLFIRINOX or gemcitabine plus capecitabine resulted in similar OS durations, and significantly better than neoadjuvant 50.4‐Gy capecitabine‐based chemoradiotherapy 256 . These clinical trials along with other studies question whether the addition of radiotherapy in NAT is beneficial or may actually be detrimental 4,177,257 . Consequently, given the lack of conclusive evidence on the effects of radiotherapy in NAT, we suggest that the use of radiotherapy in NAT should be limited to RCTs only.…”
Section: Selecting Pdac Nat Regimens and The Use Of Radiotherapymentioning
confidence: 92%
“…Pancreatic ductal adenocarcinoma (PDAC) was the fourth leading cause of cancer‐related death in 2021 and is projected to be second by 2030 1,2 . It is associated with a poor 5‐year survival rate of 11%, most likely due to its tendency to disseminate early‐on, lack of effective systemic therapy, and delayed response 3–5 . Surgical resection is the only cure for PDAC currently, but patients often present with metastatic disease or unresectable primary tumors at diagnosis 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Overall survival (OS) and recurrence free survival (PFS) were associated with the number of chemotherapy cycles received preoperatively [54]. Patients with pancreatic cancer who received ≥67% of the recommended chemotherapy cycles or ≥56% cumulative relative dose intensity had improved OS [55].…”
Section: Impact Of Chemotherapeutic Course and Dosementioning
confidence: 99%